Recontextualizing Satire of Brahmanical Dharmaśāstra in the Aggañña Sutta - Hiltebeitel, Alf (Religions of South Asia, 2009)
This article takes up passages that allow for comparison of Buddhist and Brahmanical ‘law’ in dharmaśāstra (including the early dharmasūtras) and Vinaya. The discussion of Vinaya draws on Steven Collins’s demonstration of Vinaya allusions in the Aggañña Sutta. The article revisits the advocacy for a pre-Mauryan dating of this sutta, arguing that it is unlikely. It proposes that we redirect discussions of the Aggañña Sutta’s satiric and humorous allusions to Brahmanical law and practices to focus on the moment that involves the building of houses. And, taking this sutta to refer to written ‘books’, it challenges scholarly insistence on its orality.